HUBUNGAN PENDAPATAN EKONOMI DENGAN TINGKAT DEPRESI GURU SELAMA WORK FROM HOME PADA MASA PANDEMI COVID-19: The Relationship of Economic Revenue with Teacher Depression Dures for Work from Home in Covid-19 Pandemic Periods - Leonita, Acknes; Mandagi, Ayik Mirayanti; Fakhira, Amira Dhisa; Rahmasari, Nadiyah (Lembaga Penelitian dan Terapan untuk Kesehatan Jiwa (Lenterakaji), 2021)
ABSTRACTThe Covid-19 pandemic has prompted the government to adopt a work from home policy. Not only has an impact on the economic sector during the Covid-19 pandemic, but impact on the education sector. The learning activities are also conducted online. During the Covid-19 pandemic, rates of depression may increase due to social isolation. The purpose of this research determined the relationship between economic income and the level of teacher depression while WFH during the Covid-19 pandemic in Jabodetabek. This research uses a quantitative descriptive with a cross-sectional study design theory of Isac Michael I. Data was collectedin by distributing questionnaires, order to obtain a sample of 100 teachers. Based on the results of statistical tests used the Chi-square test, the data obtained p-value = 0.523, it means that there was no relationship teacher economic income and the level of depression. The conclusion from the results of the research was that most teachers experienced a reduction in salaries during the Covid-19 pandemic, but based on statistical results there was no relationship economic income and the level of teacher depression. Recommendation that teachers can do is to improve time management properly during WFH in order to prevent depression during the Covid-19 pandemicKeywords: Economic Income, Depression Level, Work from Home. ABSTRAKPandemi Covid-19 mendorong pemerintah untuk mengadopsi kebijakan bekerja dari rumah (WFH). Tidak hanya berdampak pada sektor ekonomi dimasa pandemi Covid-19, tetapi juga berdampak pada sektor pendidikan. Kegiatan belajar mengajar juga dilakukan secara online. Selama pandemi Covid-19, tingkat depresi dapat meningkat karena isolasi sosial. Tujuan penelitian ini adalah untuk mengetahui hubungan pendapatan ekonomi dengan tingkat depresi guru selama WFH pada pandemi Covid-19 di Jabodetabek. Penelitian ini menggunakan metode deskriptif kuantitatif dengan desain studi cross sectional menggunakan teori Isac Michael I. Pengumpulan data dilakukan secara online dengan menyebarkan kuesioner, sehingga diperoleh sampel sebanyak 100 guru. Berdasarkan hasil uji statistik chi-square diperoleh data p-value= 0,523 artinya tidak ada hubungan antara pendapatan ekonomi guru dengan tingkat depresi. Kesimpulan dari hasil penelitian didapatkan bahwa sebagian besar guru mengalami pengurangan gaji selama masa pandemi Covid-19, namun berdasarkan hasil statistik tidak terdapat hubungan antara pendapatan ekonomi dengan tingkat depresi guru. Rekomendasi yang dapat dilakukan guru adalah meningkatkan manajemen waktu dengan baik selama WFH agar dapat mencegah kejadian depresi selama pandemi Covid-19.Kata Kunci: Pendapatan Ekonomi, Tingkat Depresi, Bekerja Dari Rumah.